2019
DOI: 10.1016/j.jdermsci.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of human dermal fibroblast cells reveals potential mechanisms underlying the protective effects of visible red light against damage from ultraviolet B light

Abstract: Background: Ultraviolet B (UVB) radiation is a major cause of skin photodamage, including the damage associated with photodermatoses, aging, and cancer. Although many studies have shown that red light has photoprotective effects on skin, the mechanisms underlying these effects are still poorly understood. Objective: The aim of this study was to identify the photoprotective effects of visible red light against UVB-induced skin damage in normal human dermal fibroblast cells using a transcriptomic approach. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The propensity of melanin and carotenoids to absorb BL over other VL wavelengths suggests BL absorption to be a consequence of evolutionary selection 12 . Conversely, longer wavelengths of VL in the yellow and red spectrum, are often reported as protective against photoaging 36,42 . Radiation dose also matters, regardless of wavelength, as high doses and cumulative exposure of red light can be deleterious, while low doses of BL or broad VL/VL+IR can be protective 16,25,29,43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The propensity of melanin and carotenoids to absorb BL over other VL wavelengths suggests BL absorption to be a consequence of evolutionary selection 12 . Conversely, longer wavelengths of VL in the yellow and red spectrum, are often reported as protective against photoaging 36,42 . Radiation dose also matters, regardless of wavelength, as high doses and cumulative exposure of red light can be deleterious, while low doses of BL or broad VL/VL+IR can be protective 16,25,29,43 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, BL (425 nm) irradiation of PMA‐treated keratinocytes did not demonstrate these beneficial effects 41 . Moreover, pretreatment with red light may be photoprotective 42 . Red light (620‐690 nm; max 660 nm; 60 J/cm 2 ) was found to upregulate genes involved in response to UVB (312 nm; 0.1 J/cm 2 )‐induced oxidative stress, DNA damage, inflammation and wound healing in human dermal fibroblasts 42 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…19 Therefore, longer exposure to high-energy blue light can also increase the amount of DNA damage, cell and tissue death, and injury, causing skin barrier damage, hyperpigmentation, and photoaging. 20 Conversely, red light is often reported to prevent photoaging, 21 but attention needs to be paid to the potential harm that long-term exposure to high doses of red light.…”
Section: Adverse Effects and Skin Pigmentationmentioning
confidence: 99%
“…It has been shown that red light protects against UV-induced DNA damage, which enhances the physical interaction of apyrimidinic endonuclease 1 (APE1) with GADD45A, a protein that plays an important role in base excision repair (Kim et al 2017 ). Furthermore, red light contributes to protecting human dermal fibroblasts against UVB by regulating the expression level of specific genes related to redox balancing and DNA base excision repair (Kim et al 2019 ). These data indicate that red light may be beneficial for the skin and potentially useful in photo-medical applications, such as accelerating wound repair.…”
Section: Introductionmentioning
confidence: 99%